Jan Paweł II a demokracja - Ossowski, Szymon (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2007)
The Author observes a certain paradox: on the one hand John Paul II sharply criticized modern liberal democracy, but on the other such words were uttered by the man who took credit for an immense, if not decisive, contribution to the collapse of Communism and the birth of democracy in Central and Eastern Europe. This contradiction, however, is only apparent since John Paul II, and the Catholic Church, perceived and defined democracy in a particular way. Their way is in many aspects contradictory to the principles of a modern model of democracy, that is liberal democracy, prevailing in Europe and elsewhere.
John Paul II and democracy